2018
DOI: 10.26444/aaem/81716
|View full text |Cite
|
Sign up to set email alerts
|

Differences in myoelectric manifestations of fatigue during isometric muscle actions

Abstract: Change in sEMG amplitude during isometric exercise may be related to muscles fatigue. The use of fatigue indices, based on sEMG amplitude, as an objective indicator of the efficacy of an endurance training programme for sportsmen requires further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Even though the literature 23 point to a higher incidence of muscle fatigue in isometric exercises, the absence of such phenomenon in the present study may be related to the time sets chosen for the static contractions. It is believed that 10 and 15 seconds of isometric exercises in the suprahyoid musculature of young women without speech-language-hearing complaint, even in three repetition series, do not deposit enough substrates inside the muscles to decrease the action potential MF.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Even though the literature 23 point to a higher incidence of muscle fatigue in isometric exercises, the absence of such phenomenon in the present study may be related to the time sets chosen for the static contractions. It is believed that 10 and 15 seconds of isometric exercises in the suprahyoid musculature of young women without speech-language-hearing complaint, even in three repetition series, do not deposit enough substrates inside the muscles to decrease the action potential MF.…”
Section: Discussionmentioning
confidence: 58%
“…Another factor that may have influenced it is the type of muscle fatigue analysis used in this study, as it was based on the simple behavior of the electromyographic MF signal 22 . The international literature 23 increasingly points to different approaches to muscle fatigue analysis, still trying to find which index best describes this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of individual peculiarities of kinematics and kinetics when performing 'non-standard' tests can be useful in coaching work for the development of individual training plans. Gawda et al have demonstrated that change in sEMG amplitude during isometric exercise could be related to muscles fatigue [17]. The use of various indices [18] and those based on sEMG amplitude, as an objective indicators of the efficacy of training process in athletes and motor programming phenomenon in humans requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, fatigue and fatigability can be evaluated by means of dynamometers which measure the global muscular strength at rest and following efforts. Fatigue can also be directly quantified by global and kinetic surface EMG 12 especially by means of mathematical treatment of the EMG signal (area under the curve [AUC], spectral analysis, mean power frequency, and root mean square [RMS]).…”
Section: Introductionmentioning
confidence: 99%